Penyuluhan Penambangan Batugunung Kepada Pengusaha Tambang Batu Daerah Kamara – Bottolai Kecamatan Barru Kabupaten Barru - Kaharuddin - Mamma; Haerany Sirajuddin; Asri Jaya; Fauzi Arifin; Ulva Ria Irfan; Musri Ma Waleda; Busthan Azikin; Hamid Umar; Ilham Alimuddin (Faculty of Engineering UNHAS, 2021)
The need for building materials is increasingly felt and expanded in line with the development of cities and regions, on the other hand mining activities can affect and damage the environment, such as what happened in the Barru, Sabangnaeri and Bottolai Rivers, where the former mines were left without reclamation. Based on this, a team from the Department of Geological Engineering, Hasanuddin University Makassar conducted counseling on batugunung mining to stone mining entrepreneurs in the Kamara - Bottolai area, Barru district in the form of Tri Dharma Perguruan Tinggi. This activity is expected to contribute, especially to stone mining entrepreneurs, to increase income and environmental safety. From the results of the field survey, several alternative materials of higher quality than currently managed (ultramafic rocks) were obtained for the community, namely dacite, andesite - trachea, diorite and limestone, scattered in several places in Barru Regency. The objectives of this community service activity are to: a. provide knowledge of rock quality and alternative locations; b. Provide technical guidance and mining work safety; c. Provide an understanding of environmental issues and the impact of mining